Islamic Legal Communication In The Determination Of Wali Adhal: A Comparative Study Of Indonesia And Morocco - Inda Brilliant; Dzulfikar Rodafi; Shofiatul Jannah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study analyzes how Islamic legal communication is applied in the determination of wali adhal in Indonesia and Morocco using a comparative case study approach. The goal is to understand the implementation of maqasid al-sharia in both legal systems, especially regarding women's rights in marriage. Data was collected through case analysis, official documents, and interviews with religious court judges. The results show that Indonesia resolves the case of guardian rejection through the appointment of a guardian judge, which illustrates a reactive yet adaptive ijtihad-based legal response. In contrast, Morocco adopted structural legislative reforms by granting adult women the right to marry without guardianship, rooted in a maqasid-oriented reinterpretation of family law. This contrast shows two models of Islamic law reform: Indonesia's case-based judicial policy and Morocco's proactive law. This study contributes to Islamic legal theory by integrating maqasid al-sharia and legal communication to explain how state institutions mediate and transmit Islamic legal values in contemporary family law.